In the Making of Salafi-Based Islamic Schools in Indonesia - Jamhari Makruf; Saifudin Asrori (Al-Jami'ah: Journal of Islamic Studies, 2022)
The Salafi manhaj (method) is emerging as a new form of Islamic education, in addition to the existing pesantren (Islamic boarding school) and madrasah (Islamic school) education systems, both of which have long histories in Indonesia. The presence of these schools reflects Salafi efforts to achieve “purification of Islam” though adherence to the idea of returning to the ‘authentic Islam’ as practiced by the early generations of Muslim. Salafi manhaj schools are also part of a transnational Islamic movement that has purposely spread ideas and movements from the Middle East around the world, including to Indonesia. Over time, these schools have developed into two models: Integrated Islamic Schools and Salafi manhaj pesantrens. Both aim to instill Islamic tenets that comply with the Salafi manhaj and disseminate and incorporate such tenets in the religious practices of Indonesian Muslims, although the Integrated Islamic Schools are more inclusive and teach aspects of the conventional state curriculum too. This article challenges previous findings that the influence of Salafi education has faded in Indonesia as efforts to combat Islamist terrorism globally have increased, arguing that Salafi educators have been strategic and effective in promoting their approach to religious education.[Manhaj Salafi merupakan model pendidikan Islam yang baru muncul melengkapi keberadaan model lama, pendidikan pesantren dan madrasah yang keduanya mempunyai sejarah panjang di Indonesia. Kehadiran sekolah Salafi mencerminkan usaha untuk ‘pemurnian Islam’ melalui ketaatan pada konsep mengembalikan ‘Islam autentik’ yang dipraktikkan oleh generasi awal muslim. Sekolah manhaj Salafi merupakan bagian dari gerakan Islam transnasional yang bertujuan menyebarkan ide dan gerakan asal Timur Tengah ke seluruh dunia, termasuk Indonesia. Sejauh ini mereka mengembangkan dua model yaitu sekolah Islam terpadu dan pesantren manhaj salafi. Keduanya menerapkan prinsip Islam yang selaras dengan manhaj Salafi serta menyebarluaskan prinsip tersebut dalam praktik keagamaan muslim di Indonesia, meski sekolah Islam terpadu tersebut juga lebih inklusif dan menerapkan kurikulum standar nasional. Artikel ini menantang tesis sebelumnya yang menyatakan bahwa pengaruh pendidikan Salafi di Indonesia luntur oleh peningkatan usaha memerangi teroris global. Namun pada kenyataannya adalah pendidik Salafi mempunyai strategi yang efektif dalam mempromosikan pendekatannya dalam pendidikan keagamaan.]